The Proapoptotic Gene Bad Regulates Brain Development via p53-Mediated Stress Signals in Zebrafish - Jo-Chi Hung (MDPI AG, 2021)
Studies have shown that the BH3-only domain Bad regulates brain development via the control of programmed cell death (PCD), but very few studies have addressed its effect on the molecular signaling of brain development in the system. In this work, we examined the novel role of zebrafish Bad in initial programmed cell death for brain morphogenesis through the priming of p53-mediated stress signaling. In a biological function study on the knockdown of Bad by morpholino oligonucleotides, at 24 h post-fertilization (hpf) Bad defects induced abnormal hindbrain development, as determined in a tissue section by means of HE staining which traced the damaged hindbrain. Then, genome-wide approaches for monitoring either the upregulation of apoptotic-related genes (11.8%) or the downregulation of brain development-related genes (29%) at the 24 hpf stage were implemented. The p53/caspase-8-mediated apoptotic death pathway was strongly involved, with the pathway being strongly reversed in a p53 mutant (p53M214K) line during Bad knockdown. Furthermore, we propose the involvement of a p53-mediated stress signal which is correlated with regulating Bad loss-mediated brain defects. We found that some major genes in brain development, such as crybb1, pva1b5, irx4a, pax7a, and fabp7a, were dramatically restored in the p53M214K line, and brain development recovered to return movement behavior to normal. Our findings suggest that Bad is required for (PCD) control, exerting a p53 stress signal on caspase-8/tBid-mediated death signaling and brain development-related gene regulation.